O15 Maintaining musculoskeletal health: a randomised controlled trial of cognitive behaviour therapy among people at high risk of developing chronic widespread pain. (20th April 2020) - Macfarlane, Gary J; Beasley, Marcus; Scott, Neil; McNamee, Paul; McBeth, John; Prescott, Gordon; Jones, Gareth T; Hannaford, Phil; Basu, Neil; Keeley, Phil; Lovell, Karina
Abstract: Background: Cognitive behaviour therapy (CBT) is effective in the management of fibromyalgia (and its characteristic feature chronic widespread pain (CWP). CBT is recommended in all recent major fibromyalgia management guidelines. From large-scale epidemiological studies, prediction models are available which identify groups at high-risk of developing CWP. We now test whether it is possible to prevent onset of CWP and/or change factors associated with its onset. Methods: A randomised controlled trial of CBT delivered by telephone plus usual care (tCBT) was tested against usual care alone (UC). Eligible adults aged at least 25 years were identified by a survey of persons registered with sixteen general practices across Scotland. Respondents reporting regional pain (not CWP) for which they had recently consulted their GP and at least 2 items from a previously validated 'high risk' profile (Somatic Symptom Scale, Sleep Problem Scale, Illness Behaviour Scale) were invited to participate. tCBT was delivered across 6 sessions over 8 weeks with booster sessions 3 and 6 months after treatment start. Primary outcome was CWP at 12 months. Secondary outcomes were risk profile measures: fatigue (Chalder Fatigue Scale), Patient Global Impression of Change (PGIC: 7 categories), psychological distress (General Health Questionnaire) and quality of life (EQ-5D-5L) also at 12 months. Analysis used logistic, ordinal logistic or linear regression depending on outcome variable type; expressed as an effect size with 95% confidence interval. Results: 1, 002 people were randomised, with equal numbers assigned to each arm of the trial: 59% of participants were female, with a median age of 59 (range 25-91) years. 66% of tCBT participants completed treatment and 83% of all participants provided follow-up data at 12 months. There was no difference in the proportion with CWP at 12 months (tCBT 18.0% v. UC 17.5%). There were improvements (all favouring tCBT) in Illness Behaviour Score (mean difference (md) -0.83; -1.55, -0.11), Sleep Problem Scale (md -0.90; -1.45, -0.36), psychological distress (Odds Ratio (OR) per category 0.65; 0.50, 0.85), EQ-5D-5L (md 0.024; 0.009, 0.039), Chalder Fatigue Scale (md -1.05; -1.66, -0.44) and PGIC (OR per category 0.51;0.39, 0.67). Specifically 30.2% of those receiving tCBT reported their health as much or very much better, compared to 17.3% of those receiving UC. Conclusion: This first-ever large-scale trial of prevention, aimed at persons at high risk, has shown tCBT does not change the likelihood of CWP onset but does improve the underlying risk profile for developing the condition as well as improving distress, fatigue and quality of life. Those receiving tCBT were, 12 months later, significantly more like to consider their health was better. This trial provides evidence for extending the group of people considered to benefit from CBT. Disclosures: G.J. Macfarlane None. M. Beasley None. N. Scott None. P. McNamee None. J. McBeth None. G. Prescott None. G.T. Jones None. P. Hannaford None. N. Basu None. P. Keeley None. K. Lovell None.